2013
DOI: 10.1016/j.jviromet.2013.06.027
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for diagnosis of bovine coronavirus using a reverse transcription recombinase polymerase amplification assay

Abstract: Bovine coronavirus (BCoV) is an economically significant cause of calf scours and winter dysentery of adult cattle, and may induce respiratory tract infections in cattle of all ages. Early diagnosis of BCoV helps to diminish its burden on the dairy and beef industry. Real-time RT-PCR assay for the detection of BCoV has been described, but it is relatively expensive, requires well-equipped laboratories and is not suitable for on-site screening. A novel assay, using reverse transcription recombinase polymerase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
77
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 24 publications
2
77
1
4
Order By: Relevance
“…As previously reported in a study using an HIV-1 RPA assay, nine mutations within the RPA primers and the exo-probe did not affect the assay performance (Boyle et al, 2013) and in a foot and mouth disease virus RT-RPA assay, up to five mutations were tolerated (Abd El Wahed et al, 2013a). In addition, the position of the mismatches did not influence the clinical sensitivity of the RT-RPA assay (Abd El Wahed et al, 2013a;Amer et al, 2013). Altogether, this indicates that RT-RPA detection is a reliable tool even in the face of new emerging virus variants in the field.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…As previously reported in a study using an HIV-1 RPA assay, nine mutations within the RPA primers and the exo-probe did not affect the assay performance (Boyle et al, 2013) and in a foot and mouth disease virus RT-RPA assay, up to five mutations were tolerated (Abd El Wahed et al, 2013a). In addition, the position of the mismatches did not influence the clinical sensitivity of the RT-RPA assay (Abd El Wahed et al, 2013a;Amer et al, 2013). Altogether, this indicates that RT-RPA detection is a reliable tool even in the face of new emerging virus variants in the field.…”
Section: Discussionsupporting
confidence: 58%
“…However, it has some fundamental limitations; real-time RT-PCR requires a sophisticated thermal cycler and a complicated experimental setup. In addition, the RT-PCR assay has a runtime of 90 min (Abd El Wahed et al, 2013a;Aryan et al, 2010;Bachmann et al, 2009 Recombinase polymerase amplification (RPA) has been developed for the rapid diagnosis of different pathogens (Abd El Wahed et al, 2013a,b;Amer et al, 2013;Piepenburg et al, 2006). It has shown equal sensitivity to real-time RT-PCR (Chow et al, 2008;Vincent et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These earlier studies used an RNA standard to determine analytical sensitivity and showed RT-RPA detection limits <1 LGC for bovine coronavirus9, and Rift Valley fever, Ebola, Marburg, Sudan and Sigma viruses2930. This is 2 LGC better than the limit of detection reported for our assay.…”
Section: Discussionmentioning
confidence: 52%
“…RPA uses bacterial recombinase enzymes to anneal primers to template DNA for extension and amplification by an isothermal polymerase67. The basic RPA platform has been used in concert with a reverse transcriptase and a fluorescent probe system for real time detection of viral pathogens with RNA genomes89. Its use of sequence repair enzymes theoretically provides a higher fidelity than RT-qPCR67, although the assay’s sensitivity to matrix-associated inhibitors is poorly characterized.…”
mentioning
confidence: 99%
“…These methods offer simple and rapid detection systems, with high specificity and sensitivity and are suitable for field diagnosis and poorly equipped laboratories (Amer et al, 2013;Boyle et al, 2013;Escadafal et al, 2014). RPA tests have been described recently for the diagnosis of important plant viruses such as Little cherry virus 2 (Mekuria et al, 2014) and Plum pox virus .…”
Section: Introductionmentioning
confidence: 99%